Nomination of insurance policy for Singaporean Muslims - Suhaili Alma’amun; Mohd Khairy Kamarudin (Penerbit Universiti Kebangsaan Malaysia, 2014)
The permissibility of a revocable nomination of insurance policies is the recent fatwa issued by the Fatwa Committee of Islamic Religious Council of Singapore (MUIS). This validation is derived by making an analogy between hibah and its revocable nomination. The fatwa has been changed with the aim to harmonise the Syariah law with Insurance Act S49L and simplify the estate administration and distribution process for Singaporean Muslims. In Malaysia, hibah of takaful benefits has been employed by the takaful providers and the operational framework varies across these takaful providers. Hibah of takaful benefits has been in operation for sometime in the absence of fatwa that validates the operational framework of this product at the national level. This study aims to explore the revocable nomination of insurance policies for Muslims in Singapore by means of semi-structured interviews and content analysis on secondary data namely statutes and fatwas. This study finds that the purpose of this fatwa amendment is to reinforce the method used to meet the objective of Islamic estate planning of Muslims’ domicile in Singapore taking into account that civil law supersedes the Islamic law. Fatwa issued in Singapore also applies to takaful funds but the fatwa treats both accounts in takaful funds similarly. Unlike Malaysia, the heritability of tabarru’ funds in takaful is still debatable. The fatwa is non-binding and thus, it raises the concern of a conflict existing between the existing laws and this fatwa which finally challenges the extent to which the fatwa is applicable. The current fatwa has received various feedbacks from the Islamic estate planners in Singapore and the suggestion of considering an additional legal document for the so-called ‘contemporary hibah’ is also highlighted. This study suggests that both countries benefit can from each other’s practice.